2019
DOI: 10.1088/1475-7516/2019/11/026
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet freeze-in and non-standard cosmologies

Abstract: A notable feature of UV freeze-in is that the relic density is strongly dependent on the highest temperatures of the thermal bath, and a common assumption is that the relevant "highest temperature" should be the reheating temperature after inflation T RH . However, the temperature of the thermal bath can be significantly higher in certain scenarios, reaching a value denoted T max , a fact which is only apparent away from the instantaneous decay approximation. Interestingly, it has been shown that if the operat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 80 publications
2
98
0
Order By: Relevance
“…In particular, it has been observed that if the DM is produced during the transition from matter to radiation domination via an interaction rate that scales like γ(T ) ∝ T n , for n > 12 the DM abundance is enhanced by a boost factor proportional to (T max /T rh ) n−12 [66], whereas for n ≤ 12 the difference between the standard UV freeze-in calculation differ only by an O(1) factor from calculations taking into account non-instantaneous reheating. More recently, it has been highlighted that the critical mass dimension of the operator at which the instantaneous decay approximation breaks down depend on the equation of state ω, or equivalently, to the shape of the inflationary potential at the reheating epoch [67][68][69]. Therefore, the exponent of the boost factor becomes (T max /T rh ) n−nc with n c ≡ 6 + 2 3−ω 1+ω , showing a strong dependence on the equation of state [67].…”
Section: Beyond the Sudden Decay Approximation Of The Inflatonmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been observed that if the DM is produced during the transition from matter to radiation domination via an interaction rate that scales like γ(T ) ∝ T n , for n > 12 the DM abundance is enhanced by a boost factor proportional to (T max /T rh ) n−12 [66], whereas for n ≤ 12 the difference between the standard UV freeze-in calculation differ only by an O(1) factor from calculations taking into account non-instantaneous reheating. More recently, it has been highlighted that the critical mass dimension of the operator at which the instantaneous decay approximation breaks down depend on the equation of state ω, or equivalently, to the shape of the inflationary potential at the reheating epoch [67][68][69]. Therefore, the exponent of the boost factor becomes (T max /T rh ) n−nc with n c ≡ 6 + 2 3−ω 1+ω , showing a strong dependence on the equation of state [67].…”
Section: Beyond the Sudden Decay Approximation Of The Inflatonmentioning
confidence: 99%
“…More recently, it has been highlighted that the critical mass dimension of the operator at which the instantaneous decay approximation breaks down depend on the equation of state ω, or equivalently, to the shape of the inflationary potential at the reheating epoch [67][68][69]. Therefore, the exponent of the boost factor becomes (T max /T rh ) n−nc with n c ≡ 6 + 2 3−ω 1+ω , showing a strong dependence on the equation of state [67]. Subsequent papers have explored the impact of this boost factor in specific models [4,[70][71][72][73][74][75][76][77][78][79][80].…”
Section: Beyond the Sudden Decay Approximation Of The Inflatonmentioning
confidence: 99%
“…In a more realistic picture, in which the instantaneous decay approximation is not used for reheating, the SM bath temperature may initially display a temperature much higher than T rh at onset of the radiation domination [67]. UV freeze-in is highly sensitive to the dynamics of the thermal bath during the intermediate period between inflation and radiation domination [68,69] and, therefore, it is natural to be analyzed within a specific heating setup (for related studies, see e.g. refs.…”
Section: Jhep04(2021)061mentioning
confidence: 99%
“…Thereby, in this paper, we explore another avenue. We assume dark sector particles start with zero abundance in the early universe and they get produced through the freezein mechanism [66][67][68][69][70][71][72]. Consequently, in our setup, we need the maximum temperature T max to be smaller than m Φ i so that they are not produced in the early universe.…”
Section: Modelmentioning
confidence: 99%